Consensus guidelines for the management of treatment-naïve chronic lymphocytic leukaemia in Singapore (2024) - Yeow Tee Goh; Yvonne Loh; Esther Chan; Yuh Shan Lee; Venkata Sreekanth Sampath; Daryl Tan; Shin Yeu Ong; Chandramouli Nagarajan (Annals, Academy of Medicine, Singapore)
Introduction: Chronic lymphocytic leukaemia (CLL) has a heterogeneous disease course and a variable prevalence across populations. Appropriate management for achieving optimal outcomes requires consideration of multiple factors, including disease-related factors like genomic alterations, patient characteristics and fitness, availability and access to treatments, and logistics/cost. This review aims to provide comprehensive and pragmatic recommendations for the management of treatment-naïve (TN) CLL that are relevant to Singapore’s clinical context. Method: Clinical consensus statements were developed by an expert panel of haematologists from Singapore through a 2-round modified Delphi process. Statements were drafted using recent evidence-based guidelines and published literature. Panel members reviewed draft statements, provided anonymised feedback and proposed modifications where relevant. A physical meeting was held to facilitate discussion, voting and endorsement of the final consensus statements. Results: The final consensus included 15 statements covering major TN CLL patient subsets. The recommendations highlight the importance of molecular testing for key biomarkers, where available/accessible, to guide initial therapy. Due to the superior efficacy of targeted agents (Bruton's tyrosine kinase inhibitors [BTKis] and B-cell lymphoma 2 inhibitors [BCL2is]), sthese are favoured over standard chemotherapy or chemotherapy-immunotherapy, especially for patients with del(17p) or TP53 mutation, and less fit patients. Conclusion: These consensus statements provide practical recommendations for the current management of TN CLL patients in Singapore and similar healthcare systems based on up-to-date evidence. Regular updates to treatment guidelines are important to ensure responsiveness to emerging evidence and evolving clinical practices and to improve patient outcomes and quality of life.